2007
DOI: 10.1021/bi700227g
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Gene Expression with Locked Nucleic Acids (LNAs) That Target Chromosomal DNA

Abstract: Oligonucleotides containing locked nucleic acid bases (LNAs) have increased affinity for complementary DNA sequences. We hypothesized that enhanced affinity might allow LNAs to recognize chromosomal DNA inside human cells and inhibit gene expression. To test this hypothesis, we synthesized antigene LNAs (agLNAs) complementary to sequences within the promoters of progesterone receptor (PR) and androgen receptor (AR). We observed inhibition of AR and PR expression by agLNAs but not by analogous oligomers contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…We observed inhibition of PR expression by conjugates 4, 5, and 7 containing eight, ten, or twelve lysines respectively ( Inhibitory agPNA-peptide conjugates 4, 5, and 7 blocked expression of both PR-B and PR-A, a result that had been observed previously with agPNAs delivered into cells in complex with DNA and lipid (9) as well as with siRNAs (duplex RNAs that are complementary to mRNA) or antigene RNAs (agRNAs, duplex RNAs that are complementary to promoter DNA) (29,30). Inhibition of both PR-B and PR-A was also observed by antigene locked nucleic acid (LNA) oligomers (31). These data reveal a linkage between reduced expression of PR-B and PR-A regardless of the chemical properties of the oligomers used (PNA, duplex RNA, LNA), target sequence (mRNA or promoter DNA), and the method of cellular delivery (cationic lipid or attached cationic peptide).…”
Section: Antigene Inhibition By Pna-lysine Conjugatessupporting
confidence: 60%
“…We observed inhibition of PR expression by conjugates 4, 5, and 7 containing eight, ten, or twelve lysines respectively ( Inhibitory agPNA-peptide conjugates 4, 5, and 7 blocked expression of both PR-B and PR-A, a result that had been observed previously with agPNAs delivered into cells in complex with DNA and lipid (9) as well as with siRNAs (duplex RNAs that are complementary to mRNA) or antigene RNAs (agRNAs, duplex RNAs that are complementary to promoter DNA) (29,30). Inhibition of both PR-B and PR-A was also observed by antigene locked nucleic acid (LNA) oligomers (31). These data reveal a linkage between reduced expression of PR-B and PR-A regardless of the chemical properties of the oligomers used (PNA, duplex RNA, LNA), target sequence (mRNA or promoter DNA), and the method of cellular delivery (cationic lipid or attached cationic peptide).…”
Section: Antigene Inhibition By Pna-lysine Conjugatessupporting
confidence: 60%
“…LNA modifications within a TFO can increase the binding affinity to the target duplex DNA, and can increase resistance to digestion by nucleases [73]. Beane et al, have demonstrated that LNAs can recognize chromosomal target sequences and efficiently block endogenous expression of the progesterone and androgen receptors [74]. An LNA analogue ENA, containing a 2'-O, 4'-Cethylene bridge has also been reported to form stable triplex at physiological pH [75].…”
Section: Chemical Modifications Of Tfosmentioning
confidence: 99%
“…LNA bases contain a methylene bridge that connects the 2 0 -oxygen of the ribose with the 4 0 -carbon, which makes it more stable than a regular oligonucleotide and suitable for therapeutic application (Beane et al 2007, Mook et al 2007). LNA-ASO binds to RNA, prevents transcription, and activates RNAse H resulting in cleavage of the target RNA molecule (Petersen & Wengel 2003, Vester & Wengel 2004.…”
Section: Apoptosis Of Neuroblastoma Cell Lines After Birc5 Knock Downmentioning
confidence: 99%